Back to a responsible responsiveness? The crisis and challenges facing European political elites: the 2017 Peter Mair Lecture. Issue 1 (2nd January 2020) - Verzichelli, Luca
ABSTRACT: In his later writings, Peter Mair elaborated on the deficit of responsiveness showed by «mainstream» political elites, vis-à-vis the extremely responsive (but largely irresponsible) attitudes of a number of new challengers and populist leaders. This concern was expressed by Mair, in his posthumous volume Ruling the void, with the notion of the «withdrawal of the elites». This article moves from these concerned considerations, confirming that in the delicate scenario of the European Union, responsible domestic politicians still seem to be significantly distant from the positions of the general public. Actually, the difficulties of the elites to act responsibly became more and more evident in the past few years, when the consequence of the great recession have amplified popular mistrust and pushed representative politicians (even those belonging to traditional and Pro-Europeanist parties) to negative evaluations about policy coordination in the EU and a possible reduction of domestic sovereignty. Using fresh data about the attitudes of politicians and mass public, the article discusses the nature of such a difficult situation for large strata of the European domestic political elites, elaborating in the final part a few conditions to build a new phase of elite sustainability in Europe.